2019
DOI: 10.1039/c8ra09783f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tetragonal to cubic phase transition on the upconversion luminescence properties of A/B site erbium-doped perovskite BaTiO3

Abstract: At the critical temperature, B-site doping with erbium shows abnormal upconversion efficiency as a function of temperature in perovskite crystals, which was attributed to the symmetry of the crystalline structure around the erbium ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Such a significant change in the band intensity ratio I SHG /I UCL is due to the intrinsic phase transition of the randomly‐oriented (nonpolarized) perovskite crystals, [ 42 ] from the broken inversion symmetry to inversion symmetry, which is well confirmed for BaTiO 3 in different reports. [ 34,36,42,43,50–52 ] The relative change in the I SHG /I UCL ratio is associated with the SHG process, which is forbidden in the cubic phase of BaTiO 3 (centrosymmetric structure). However, the SHG signal does not completely disappear (see Figure 2b), even at the highest temperature measured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a significant change in the band intensity ratio I SHG /I UCL is due to the intrinsic phase transition of the randomly‐oriented (nonpolarized) perovskite crystals, [ 42 ] from the broken inversion symmetry to inversion symmetry, which is well confirmed for BaTiO 3 in different reports. [ 34,36,42,43,50–52 ] The relative change in the I SHG /I UCL ratio is associated with the SHG process, which is forbidden in the cubic phase of BaTiO 3 (centrosymmetric structure). However, the SHG signal does not completely disappear (see Figure 2b), even at the highest temperature measured.…”
Section: Resultsmentioning
confidence: 99%
“…[ 32,33 ] With increasing temperature, different regions of the material change their crystallographic orientations, altering the crystal structure symmetry, and the phase transition (tetragonal to cubic) occurs, leading to enormous variability in the electric and spectroscopic features of the material. [ 34,35 ] Therefore, it is of crucial importance to determine the crystal symmetry transformation and the corresponding temperature in a noninvasive, rapid and simple way. [ 35–38 ]…”
Section: Introductionmentioning
confidence: 99%
“…For the majority of materials, the lattice expands with increasing temperature, accompanied by potential ionic disordering, defect formation, polymorphic transformation, etc. In practice, temperature influences the upconversion emissions from many aspects, including local structure, 113 electron−phonon coupling, 114 surface status, 115 and thermal population that complies with Boltzmann distribution law. 116 The influences from the local structure are emphasized in this section.…”
Section: Engineering Local Structure By External Field Regulationmentioning
confidence: 99%
“…The bonds of a-CsPbI 3 are stretched slightly along the direction of applied pulling forces prior to the formation of cracks or voids in the materials for energy compensation, which is similar to an earlier observation for the transformation of a cubic to a tetragonal structure with increasing potential energy. 42,43 It is also observed that the magnitude of the pulling force influences the initiation of cracking in the material. Crack initiation occurs nearly 20 times faster at high F z values (7 pN and 35 pN) than at low F z values (0.007 pN and 0.07 pN).…”
Section: Effect Of Variation In the Magnitude Of Pulling Force F Zmentioning
confidence: 99%